2020
DOI: 10.3390/ijms21197075
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Activation and Inactivation of Mutations Inducing Cell Surface Loss of Receptor and Impairing of Signal Transduction of Agonist-Stimulated Eel Follicle-Stimulating Hormone Receptor

Abstract: In the present study, we investigated the signal transduction of mutants of the eel follicle-stimulating hormone receptor (eelFSHR). Specifically, we examined the constitutively activating mutant D540G in the third intracellular loop, and four inactivating mutants (A193V, N195I, R546C, and A548V). To directly assess functional effects, we conducted site-directed mutagenesis to generate mutant receptors. We measured cyclic adenosine monophosphate (cAMP) accumulation via homogeneous time-resolved fluorescence as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 10 publications
(46 citation statements)
references
References 51 publications
(81 reference statements)
5
40
1
Order By: Relevance
“…The present study showed that the four mutations—eLH/CGR-M398T, L457R, D564G, and D578Y—resulted in a distinctly increased cAMP response without agonist treatment, suggesting that these mutations might produce constitutively activating mutants of eLH/CGRs. Our previous observations have suggested that the same active conformations of rLHR [ 11 ], eel FSHR [ 10 ], and eFSHR [ 25 ] are involved in the stimulation of G proteins and loss of the cell-surface receptor in ligand–receptor complexes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study showed that the four mutations—eLH/CGR-M398T, L457R, D564G, and D578Y—resulted in a distinctly increased cAMP response without agonist treatment, suggesting that these mutations might produce constitutively activating mutants of eLH/CGRs. Our previous observations have suggested that the same active conformations of rLHR [ 11 ], eel FSHR [ 10 ], and eFSHR [ 25 ] are involved in the stimulation of G proteins and loss of the cell-surface receptor in ligand–receptor complexes.…”
Section: Discussionmentioning
confidence: 99%
“…To construct point mutations, we introduced the cDNA, encoding the full-length eLH/CGR using an overlap extension PCR strategy to create activating and inactivating mutants, as previously described [ 10 ]. Two different sets of PCRs were performed, and the primer sequences used in these experiments are shown in Table 5 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CHO-K1 cells were transfected using the previously reported liposome transfection method (Byambaragchaa et al 2020 ). The CHO cells were cultured in growth medium [Ham’s F-12 media supplemented with penicillin (50 U/mL), streptomycin (50 µg/mL), glutamine (2 mM), and 10% fetal bovine serum] to 80%–90% confluency in six-well plates.…”
Section: Methodsmentioning
confidence: 99%